Earthquake Distribution Along an Entire Ridge Segment of the Ultraslow Spreading Knipovich Ridge - Meier, Michaela; Schlindwein, Vera; Krüger, Frank; Czuba, Wojciech; Janik, Tomasz (2019)
The Knipovich Ridge is part of the Arctic Ridge System comprising very slow spreading ridges. In the class of ultraslow spreading ridges, the Knipovich Ridge with its full spreading velocity of 14 – 17 mm/yr is one of the slowest and most obliquely spreading ridges. Magmatic centres along the Knipovich Ridge are mostly defined by seamounts. Amagmatic segments, where tectonism dominates the spreading, act as transfer regions between magmatic centres, since transform faults are absent. The detailed spreading processes at ultraslow spreading ridges still remain unclear. We want to study tectonics and magmatism and their interplay along the Knipovich Ridge by the distribution of local seismicity at segment-scale. We further are interested in how ridge segmentation works in the absence of transform faults. Knipovich Ridge was equipped with a maximum of 30 ocean bottom seismometers along a length of 160 km. The seismometers are positioned between 75.7 and 77.2°N to both sides of the rift valley. They recorded seismicity continuously for on average 11.5 months between summer 2016 and 2017. We used the detection algorithm Lassie and a Kurtosis-based picking algorithm followed by review of the picks by an analyst. The velocity model used for location is defined by well constrained events. We present here first results of this project. We found that earthquakes are not equally distributed along the ridge axis. We observe regions of enhanced seismicity and regions with no or very little seismic activity. Focal depths undulate along the ridge axis up to depths of 20-25 km. We also found clusters of events, one in the north, close to volcanic features, and one close to station 19, south of the Logachev Seamount, a prominent volcanic edifice. The depth distribution of earthquakes reflects the boundary between brittle and ductile deformation, depending on temperature and composition of rocks. This thermal boundary has a varying depth along the rift axis and allows the focussing of melts, e.g. towards Logachev Seamount, where ...